Plasma exchange and chlorambucil in polyneuropathy associated with monoclonal IgM gammopathy. IgM-associated Polyneuropathy Study Group. - Oksenhendler, E (1995)
The study compared chlorambucil alone with chlorambucil in combination with plasma exchange in patients with polyneuropathy associated with monoclonal IgM. Forty four patients were prospectively randomly assigned, in a comparative open trial, to receive either 0.1 mg/kg/day chlorambucil orally, for 12 months or chlorambucil associated with 15 courses of plasma exchange, during the first four months of treatment. They were evaluated by a neuropathy disability score and nerve conduction studies. No difference was found between the two treatment groups. The average neuropathy disability score improved by 2.1 points from baseline (21.0 to 18.9) in the chlorambucil group and by 1.8 points (20.4 to 18.6) in the chlorambucil + plasma exchange group (P = 0.70). The mean motor nerve conduction velocity decreased from 20.0 to 18.2 m/s in the chlorambucil group and increased from 20.5 to 22.5 m/s in the chlorambucil + plasma exchange group (P = 0.51). A slight improvement of the sensory component of the neuropathy disability score (from 10.5 to 8.3) was noted in both groups (P = 0.01). At the end of the study and according to self evaluation, 15 patients--eight from the chlorambucil group and seven from the chlorambucil + plasma exchange group--reported clinical improvement, whereas 15--eight from the chlorambucil group and seven from the chlorambucil + plasma exchange group--reported clinical worsening. Neuropathy remained stable in the others. Thus plasma exchange seemed to confer no additional benefit in the treatment of polyneuropathy associated with monoclonal IgM.